G20 framework for repurposing agricultural policy support to meet global climate and food security goals - Martin, Will; Vos, Rob; Glauber, Joseph W.; Laborde Debucquet, David; Piñeiro, Valeria (T20 Indonesia, 2022)
Recent studies provide unequivocal evidence that current agricultural support policies are ineffective to achieve the multiple goals of food security, affordable healthy diets, remunerative livelihoods for farmers, and environmental protection. Repurposing of agricultural support for investing in innovations in productivity-enhancing and sustainable emission-reducing production practices and for creating the incentives for their adoption can bring significant win win-win gains for people, planet, and prosperity. However, achieving such gains will require an even-handed and internationally concerted approach to policy reform behind common objectives. The G20 is well positioned to coordinate such an approach. The brief recommends that the G20 develops a common framework for repurposing of agricultural support providing guidelines and options for a concerted approach for (i) phasing out harmful policies and investing in measures to incentivize adoption of sustainable agricultural practices and diversification of production towards more nutritious foods to ensure affordability of healthy diets and (ii) establishing a common framework and implementation mechanism for international cooperation to ensure repurposing can take place even-handedly and optimizing gains for global sustainable development. The brief further proposes that the G20 promotes the establishment of a platform to monitor and assess the impacts of repurposed agricultural support measures, identify trade-offs, and report on the progress made towards the common global objectives agreed under the G20 common framework for repurposing of agricultural support.